An ultrasonic C.W. doppler method of measurement of the blood flow velocity - T. POWAŁOWSKI (Archives of Acoustics)
This paper presents an analysis of factors affecting the results of measurement of the blood flow velocity by the ultrasonic continuous wave (O.W.) Doppler method. For the parabolic flow velocity profile the effect on the spectrum of a Doppler signal of such factors as the ratio of the width of the ultrasonic beam to the inner diameter of the blood vessel and the coincidence of the transmitted ultrasonic beam with the one received inside the blood vessel, was analyzed. To that end, two variants of the position of the transmitting transducer and the transducer receiving the ultrasonic wave, with respect to the blood vessel were considered. In the first variant the point of intersection of axes of the transmitted ultrasonic beam and of the received from the flowing blood, was outside the blood vessel. In the second variant the axes of the ultrasonic beams intersected with each other in the middle of the blood vessel, on its axis. On the basis of analysis of the spectra of a Doppler signal the value of the factor of proportionality between the frequency of zero-crossings of the amplitude of the Doppler signal, measured by a Doppler flowmeter, and the mean Doppler frequency corresponding to the moan blood flow velocity in the blood vessel, was determined. This factor is the basis for quantitative estimation of the blood flow velocity from the Doppler frequency measured by the flowmeter.